Effects of private label, store brand image, and product signature on Word of Mouth (WOM) emotion at Indomaret Point Samarinda - Fidelia Zulfaqar Putri; Herning Indriastuti (Privietlab, 2026)
This study aims to examine the influence of private label on store brand image, private label on product signature, private label on word of mouth (WOM) emotion, store brand image on word of mouth (WOM) emotion, and product signature on word of mouth (WOM) emotion at Indomaret Point Samarinda. A quantitative approach was employed, and data were collected through questionnaires distributed to 200 respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that private label has a significant effect on store brand image and product signature. Furthermore, store brand image and product signature significantly influence WOM emotion. Although private label also directly affects WOM emotion. These findings indicate that private label, store brand image, and product signature plays an important role in strengthening store identity and encouraging positive emotional responses from consumers.